Eating behaviors, depression, and anxiety levels of pre bariatric surgery patients with obesity comorbid with or without Attention deficit and hyperactivity disorder: ADHD or Major Depression? Which is more related with eating behaviors?. Issue 1 (28th October 2020) - Şahan, Ebru; Zengin Eroğlu, Meliha; Sertçelik, Sencan
Abstract: Objective: A high rate of attention deficit and hyperactivity disorder ( ADHD) has been reported in patients undergoing obesity treatment. It is controversial whether ADHD solely or its comorbid disorders account for eating behaviors associated with obesity. Methods: After presurgery psychiatric assessment, 100 severely obese patients (50 with ADHD and 50 without ADHD) were administered Adult Attention Deficit Hyperactivity Disorder Self‐Report Scale(ASRS), Wender Utah Rating Scale(WURS), Three‐Factor Eating Questionnaire(TFEQ), and Beck Depression Inventory(BDI) and Beck Anxiety Inventory(BAI). Results: Patients with obesity and ADHD had significantly greater emotional eating, susceptibility to hunger, depression, and anxiety but less restraint of eating scores than those without ADHD. Disinhibition of eating scores and presence of Binge Eating Disorder(BED) did not differ significantly between ADHD and non‐ADHD groups. Obese patients with major depression had significantly higher ASRS, WURS, TFEQ, BAI scores, disinhibition of eating control, emotional eating, susceptibility to hunger, and diagnosis of BED than nondepressed ones. Conclusions: Major depression and anxiety disorder have associations with disinhibition of eating control, emotional eating, susceptibility to hunger and BED, ADHD. Disinhibition of eating and BED did not differ according to the presence of ADHD; thus, depression was associated with eating control on more constructs than ADHD in our study. Abstract : Major Depression has associations with almost all disordered eating behaviors including disinhibition of eating control, emotional eating, susceptibility to hunger and BED, ADHD and anxiety disorder. Disinhibition of eating and BED did not differ according to the presence of ADHD in our sample; thus, depression seems to be associated with eating control on more constructs than ADHD.